The impact of political instability on inflation volatility: The case of the Middle East and North Africa region - Afnan Ghanayem; Gareth Downing; Murad Sawalha (Cogent Economics & Finance, 2023)
This study examines the impact of political instability on inflation volatility in the Middle East and North Africa (MENA) region. First, it analyzes the multidimensionality of political instability by adopting a factor analysis technique and finds five dimensions of political instability. Next, it adopts GARCH, EGARCH, and TGARCH volatility specifications to model country-specific monthly inflation data. Finally, it examines the impact of the five dimensions of political instability on GARCH conditional inflation volatility by employing the dynamic Generalized Method of Moments (GMM) panels. This paper reports both positive and negative effects of political instability on inflation volatility in the MENA region. Specifically, we show that the instability of the political regime dimension significantly increases inflation volatility, while the dimension of government instability significantly reduces inflation volatility. Our results hold for a set of robustness checks, including the MIDAS weighted conditional inflation volatility measures.
Keywords: 330; GMM; inflation volatility; MENA; Political instability